Divergent patterns of soil phosphorus discharge from water-level fluctuation zone after full impoundment of Three Gorges Reservoir, China - Zhou, Jun; Wu, Yanhong; Wang, Xiaoxiao; Bing, Haijian; Chen, Yang; Sun, Hongyang; Zhong, Zhilin (Environmental science and pollution research international, 2019)
Phosphorus (P) discharged from soils in the water-level fluctuation (WLF) zone becomes increasingly important to the water quality control of the Three Gorges Reservoir (TGR) as the decrease in P input from upstream reaches and point-source pollution. To investigate the amount of soil P discharge from the WLF zone since the full impoundment of the TGR in 2010, soil and sediment samples were collected along the altitudinal gradients (140, 150, 160, 170, and 180 m above sea level) in three transects in the middle reaches of the TGR. Soil P composition was determined by a sequential extraction procedure. Different amounts of P discharge from the WLF zone were found among three soil types because of their difference in the initial P content before impoundment, with an order of yellow earth (171.1 g m −2 ), fluvo-aquic soil (141.7 g m −2 ), and purple soil (73.8 g m −2 ). An altitudinal pattern of soil P discharge was observed with the maximum at the 170-m sites. The downward transport of exchangeable P and clay-bound P with runoff was the major path of the soil P discharge at the 170-m sites with a slope gradient > 15°. Considerable P discharge with erosion at the upper section of the WLF zone was facilitated by the longer exposure period compared with that at bottom section (150-m sites) because of the annual anti-seasonal impoundment-exposure cycles of the TGR. The transformation of Al/Fe-P and subsequent release to water was a main mechanism of the soil P discharge during the impoundment period. The altitudinal pattern of P discharge was a result of joint effects of slope gradient, soil P forms, and the anti-seasonal hydrological regime of the TGR. The results highlight the critical role of the upper section (165–175 m) in controlling the P output from the WLF zone into the water of the TGR.